Human Pleural Fluid Elicits Pyruvate and Phenylalanine Metabolism in Acinetobacter baumannii to Enhance Cytotoxicity and Immune Evasion - Rodman, Nyah; Martinez, Jasmine; Fung, Sammie; Nakanouchi, Jun; Myers, Amber L.; Harris, Caitlin M.; Dang, Emily; Fernandez, Jennifer S.; Liu, Christine; Mendoza, Anthony M.; Jimenez, Veronica; Nikolaidis, Nikolas; et al. (Frontiers in Microbiology, 2019)
Acinetobacter baumannii (Ab) is one of the most treacherous pathogens among those causing hospital-acquired pneumonia (HAP). A. baumannii possesses an adaptable physiology, seen not only in its antibiotic resistance and virulence phenotypes, but also in its metabolic versatility. In this study, we observed that A. baumannii undergoes global transcriptional changes in response to human pleural fluid (PF), a key host-derived environmental signal. Differential gene expression analyses combined with experimental approaches revealed changes in A. baumannii metabolism, affecting cytotoxicity, persistence, bacterial killing and chemotaxis. Over 1220 genes representing 55% of the differentially expressed transcriptomic data corresponded to metabolic processes, including the up regulation of glutamate, short chain fatty acid, and styrene metabolism. We observed an up regulation by 1.83 and 2.61-fold of the pyruvate dehydrogenase complex subunits E3 and E2 respectively. We also found that pyruvate (PYR), in conjunction with PF, triggers an A. baumannii pathogenic behavior that adversely impacts human epithelial cell viability. Interestingly, PF also amplified A. baumannii cytotoxicity against murine macrophages, suggesting an immune evasion strategy implemented by A. baumannii. Moreover, we uncovered opposing metabolic strategies dependent on the degree of pathogenicity of the strains, where less pathogenic strains demonstrated greater utilization of PYR to promote persister formation in the presence of PF. Additionally, our transcriptomic analysis and growth studies of A. baumannii suggest the existence of an alternative phenylalanine (PA) catabolic route independent of the phenylacetic acid pathway, which converts PA to phenylpyruvate (PP) and shuttles intermediates into styrene metabolism. This alternative route promoted a neutrophil-evasive state, as PF-induced degradation of PP significantly reduced overall human neutrophil chemotaxis in ex vivo chemotactic assays. Taken together, these data highlight A. baumannii pathoadaptabililty in response to host signals and provide further insight into the role of bacterial metabolism in virulence traits, antibiotic persistence strategies, and host innate immune evasion.